Asymmetric monetary policy effects in EMU - Volker Clausen; Bernd Hayo (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2002)
This paper uses a semi-structural dynamic modelling approach to investigate asymmetric monetary transmission in Europe. A system of equations containing reaction functions for monetary policy, output and inflation equations is simultaneously estimated for France, Germany, and Italy. Extensive cross equation tests show that relatively large differences in simulated impulse responses are still consistent with the notion that the transmission mechanism is homogeneous across the three major EMU countries. However, monetary policy impulses show a relatively stronger effect on the output gap in Italy and Germany. Out-of-sample tests do not find a structural break in the transmission mechanisms prior to EMU.
Keywords: E52; F41; 330; European Monetary Union; Monetary Policy; Semi-structural modelling; Transmissionsmechanismus; Geldpolitik; Europäische Wirtschafts- und Währungsunion; Schätzung; Frankreich; Deutschland; Italien